A yeast metabolome-based model for an ecotoxicological approach in the management of lignocellulosic ethanol stillage. Issue 1 (16th January 2019) - Roscini, Luca; Favaro, Lorenzo; Corte, Laura; Cagnin, Lorenzo; Colabella, Claudia; Basaglia, Marina; Cardinali, Gianluigi; Casella, Sergio
Abstract : Lignocellulosic bioethanol production results in huge amounts of stillage, a potentially polluting by-product. Stillage, rich in heavy metals and, mainly, inhibitors, requires specific toxicity studies to be adequately managed. To this purpose, we applied an FTIR ecotoxicological bioassay to evaluate the toxicity of lignocellulosic stillage. Two weak acids and furans, most frequently found in lignocellulosic stillage, have been tested in different mixtures against three Saccharomyces cerevisiae strains. The metabolomic reaction of the test microbes and the mortality induced at various levels of inhibitor concentration showed that the strains are representative of three different types of response. Furthermore, the relationship between concentrations and FTIR synthetic stress indexes has been studied, with the aim of defining a model able to predict the concentrations of inhibitors in stillage, resulting in an optimized predictive model for all the strains. This approach represents a promising tool to support the ecotoxicological management of lignocellulosic stillage.